Ant preference for different types of bait at sugarcane plantations in East Java, Indonesia - BAMBANG TRI RAHARDJO; FAIZ NASHIRUDDIN MUHAMMAD; YOGO SETIAWAN; AKSHA FEBRYADI; MUHAMMAD IHSAN; DENNIS WIBOWO; ITO FERNANDO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rahardjo BT, Muhammad FN, Setiawan Y, Febryadi A, Ihsan M, Wibowo D, Fernando I. 2023. Ant preference for different types of bait at sugarcane plantations in East Java, Indonesia. Biodiversitas 24:2099-2106. The occurrence of ants is important in agroecosystems since they may provide both ecosystem services or disservices depending on the species composition. Therefore, it is necessary to investigate the kind of ant species that are present in agroecosystems. This study aimed to assess the effectiveness of three types of bait to measure ant abundance and diversity in sugarcane plantations. This research was conducted from July to September 2022 in four locations in East Java, Indonesia, i.e., Karangploso, Kalipare, Gandusari, and Pasirian. At each location, one plot was determined and divided into nine subplots. Ant sampling was conducted using modified pitfall traps that may contain one type of bait or without bait as control treatment. There were three types of assayed bait, i.e., tuna, eggs, and sugar. Nine traps for each treatment were installed in each location. This study obtained 6,650 individual ants from 20 morphospecies, 16 genera, and 4 subfamilies. At each location, species richness and abundance were not significantly different among bait types. However, those variables differed between the bait groups and the control. Tuna and egg baits were preferred by ants, as indicated by the higher number of trapped individuals than in sugar bait and the control traps. The species composition of the different baits was different at all locations except Kalipare. Each ant species had a different preference for the type of bait. Formicine ants preferred sugar bait, while ponerine ants preferred tuna and egg baits. Hence, it can be concluded that the bait type selection needs to be considered for ant monitoring. Therefore, using various types of baits is recommended to monitor the assemblage of ants in an ecosystem.